Sustaining lean thinking in healthcare: case studies - Henrique, Daniel Barberato (2018)
Many hospitals have achieved high levels of lean performance only to lose it later on. These hospitals, which often achieved excellent results, neglected some specific aspects of sustaining lean improvements in their environments, and failed to maintain what was implemented. This research develops a theoretical understanding of how organizations can sustain lean in healthcare. Through the analysis of the literature, it was possible to compile 22 main critical success factors of lean sustainability in hospitals through three main pillars: people, method and tools. A comparative case study provides evidence to confirm these 22 theoretical propositions, and also to add other 5 new propositions to the framework. The proposed framework allows hospitals to conduct a structured process of change, with all the foundation needed to succeed and sustain the lean journey in the long-term. It differs from previous studies by integrating literature streams that have been previously disconnected and by specifying the components of lean healthcare sustainability. These new insights are revealed by studying hospitals after minimum 18 months of lean implementation and comparing the ones that have achieved a high level of lean sustainability with those that do not. To the best of our knowledge, this dissertation is the first to attempt to bring together the key factors that influence hospitals to sustain lean improvements in the long term. This research found evidence that external factors to the three pillars may also interfere to facilitate or difficult hospitals to achieve sustainability in their lean implementations. They are called “success variables moderators” and they are intrinsically linked to the organizational characteristics of each hospital. The variables “type of administration and financial objective” and “accreditation” have proved to influence the hospital to achieve success in its lean implementations in the long term. Another interesting conclusion that can be drawn is that although it is notorious knowledge, several points brought by the theoretical framework proved to be difficult to implement and the hospitals are failing to implement the basics.